Johnny Cash : the redemption of an American icon - Laurie, Greg (Salem Books, an imprint of Regnery Publishing, 2019)
Johnny Cash: The Redemption of an American Icon dives deep into the singer's inner demons, triumphs, and gradual return to faith. Laurie interviews Cash's family, friends, and business associates to reveal how the singer's true success came through finding the only Person whose star was bigger than his own.